A Longitudinal Study on Breastfeeding Practice among Women Living in Western Saudi Arabia - Shahbar, Anwaar; Bahijri, Suhad; Weber, Janet; Eid, Noura M.S. (International Journal of Child Health and Nutrition, 2019)
This paper presents a longitudinal study of breastfeeding at two private hospitals in Jeddah, Saudi Arabia. Soliman Fakeeh (SF) follows the WHO’s baby-friendly hospital initiative (BFHI), Saudi Germany Hospital (SGH) does not. Participants were 102 women in both hospitals (52 BFHI, 50 non-BFHI). Two semi-quantitative questionnaires, translated into Arabic, were used at baseline and one month postpartum. Results showed that most women in the study have initiated breastfeeding but turned to mixed feedings after one month. We also found that self-efficacy has the biggest influence on breastfeeding practice at one month, measured by the Breastfeeding Self-Efficacy Scale (BSES) and regardless of other variables. The BFHI made breast milk the first nutritive substance infants received and had a higher percentage of early initiation of breastfeeding than the non-BFHI. The BFHI hospital supported women to breastfeed practically and educationally. Support was provided by books, internet, and educational sessions. Yet, any effects no longer existed at one month postpartum, at which point most women had shifted to mixed feeding. There was no relationship between the BSES and BFHI status. Thus, we recommend developing breastfeeding promotion programs before delivery and at least a six-months follow-up after delivery, in addition to peer counselling approaches.